Italianness as Lived through the Body. Italian Women’s (Self-) Perception in Archival Health Columns - Lewandowska, Małgorzata J. (Doświadczanie i wyrażanie włoskości: Aspekty językoznawcze i glottodydaktyczne, 2021)
The experience of one’s own body is undoubtedly bound to certain places, environments and times. The experience of being an Italian woman is therefore different than that of being Polish, German, or American. The perception of the female body mirrors a country’s laws, a society’s level of demureness and the tolerance towards oneself and others. The work presented here stems from an interest in the representation of the female body as presented in health columns in the 1950-1965 issues of the weekly magazine “Grazia”. Through discourse analysis it is possible to obtain an image not only of the body, but also, metonymically, of Italian society at a time when Cesare Zavattini (1959) defined it as “a huge harem” made “of what is silenced and what is unuttered”. The analysis proposed herein aims at opening another perspective on Italianness, whereby “other” can be understood both as “female” (as de Beauvoir’s followers certainly would) or as “silenced” or “unuttered”. In addition to that, considering the type of corpus being analysed, the letters from the female readership offer a view on Italian women’s self-image. A perspective which is not only intimate, but also “from the inside” and that frequently has nothing to share with the image of Italian society that is common outside of Italy.